2021
DOI: 10.1177/2158244020988557
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Work Practices and Turnover Intention: Investigating the Mediating Role of Employee Morale and the Moderating Role of Psychological Capital

Abstract: This study examined the effects of high-performance work practices on turnover intention through the mediating role of employee morale. The study also examined the extent to which psychological capital could moderate the relationship between employee morale and turnover intention. With the aid of questionnaire administration, the study collected 469 valid responses from frontline employees in the hospitality sector of Ghana. Findings from the hierarchical regression analysis showed that training and empowermen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 75 publications
1
34
0
4
Order By: Relevance
“…According to previous studies, age, gender, education, and organisation tenure have been shown to explain variance in work performance and innovative work behaviour (e.g., Lei et al, 2015;Ye et al, 2015;Zhang and Long, 2016). Therefore, the effects of gender, age, education, and organisation tenure were statistically controlled to elicit their potential confounding effects.…”
Section: Control Variablesmentioning
confidence: 96%
“…According to previous studies, age, gender, education, and organisation tenure have been shown to explain variance in work performance and innovative work behaviour (e.g., Lei et al, 2015;Ye et al, 2015;Zhang and Long, 2016). Therefore, the effects of gender, age, education, and organisation tenure were statistically controlled to elicit their potential confounding effects.…”
Section: Control Variablesmentioning
confidence: 96%
“…(Nasution, 2020) menerangkan semangat kerja berpengaruh positif dan signifikan terhadap variabel kinerja. (Obeng et al, 2021) menyatakan bahwa semangat kerja dapat meningkatkan komitmen kerja pegawai sehingga kinerja industri meningkat.…”
Section: Uji Multikolinieritasunclassified
“…Organisational commitment is a job attitude known to be closely linked to employee morale, motivation and behaviour [18,19]. Individuals who have higher organisational commitment are likely to be highly motivated, expend much energy towards work, be, or desire to be, involved in the life of the organisation, engage in day-to-day work and are generally more productive as a result [18,[20][21][22][23]. Individuals who have lower organisational Educ.…”
Section: Introductionmentioning
confidence: 99%